2022
DOI: 10.3390/women2020012
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence and Pregnancy Termination among Tajikistan Women: Evidence from Nationally Representative Data

Abstract: Intimate partner violence is the most common kind of violence and a significant public health issue. The relationship between intimate partner violence and pregnancy termination among Tajikistan women was investigated in this study. The data for this research was collected from the Tajikistan Demographic and Health Survey 2017. This research has used the data of married women aged between 15 to 49 years. The findings from the study indicate that around 23.2% of married women in Tajikistan have experienced phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…As well, quarantine, fear of infection, the chaos of social networks, reduced access to health and social services, distress, misinformation, income shortage, financial loss, job loss, and limited social support are likely to raise risks of IPV in the pandemic ( 25 – 27 ). This evidence is supported by a study done in Tajikistan, which stated that intimate partner violence is significantly associated with no or primary educational status and husbands who have alcohol-drinking habits ( 71 ).…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…As well, quarantine, fear of infection, the chaos of social networks, reduced access to health and social services, distress, misinformation, income shortage, financial loss, job loss, and limited social support are likely to raise risks of IPV in the pandemic ( 25 – 27 ). This evidence is supported by a study done in Tajikistan, which stated that intimate partner violence is significantly associated with no or primary educational status and husbands who have alcohol-drinking habits ( 71 ).…”
Section: Introductionmentioning
confidence: 62%
“…A finding from Tajikistan showed that the prevalence of physical, emotional, and sexual violence was 23.2%, 15.5%, and 1.7%, respectively. In this study, the educational level and alcohol-drinking status of husbands were significantly associated with intimate partner violence ( 71 ).…”
Section: Introductionmentioning
confidence: 73%
“…An understudied and underestimated phenomenon is also violence in pregnancy. Widespread is the stereotype that pregnancy has a protective function with respect to violence [18][19][20]. The data, however, contradict this reality.…”
Section: Different Forms Of Gender-based Violencementioning
confidence: 99%
“…Further, the high levels of migration mean that Tajik wives are vulnerable to being separated from their husbands, having little-to-no financial or social support, and often left dependent on their in-laws (30). Evidence suggests that Tajik women are at high risk of domestic violence at the hands of their husband/in-laws and at least 23% of married women have experienced domestic violence (31). Violence against women and girls (VAWG) is a major problem in Tajikistan, driven by conservative gender norms, the culturally ascribed position of young women, and poverty, although there is evidence for the effectiveness of violence reduction programmes (30).…”
Section: Tajikistan Contextmentioning
confidence: 99%